2014
DOI: 10.3238/arztebl.2014.0692
|View full text |Cite
|
Sign up to set email alerts
|

Physical Examination in Child Sexual Abuse

Abstract: SUMMARYBackground: The worldwide prevalence of child sexual abuse is 12-13% (18% of girls, and just under 8% of boys). Many doctors are nevertheless unsure of the proper procedures to follow and the scientific basis of the physical findings that are associated with sexual abuse. This article is focused on the physical findings of abuse, rather than its emotional and psychiatric consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 65 publications
1
18
0
13
Order By: Relevance
“…• anal or vaginal soreness or excessive itching; • sexually-transmitted disease, an unusual discharge; • blood in urine or faeces; • pregnancy [2,5].…”
Section: Identification Of Csamentioning
confidence: 99%
See 4 more Smart Citations
“…• anal or vaginal soreness or excessive itching; • sexually-transmitted disease, an unusual discharge; • blood in urine or faeces; • pregnancy [2,5].…”
Section: Identification Of Csamentioning
confidence: 99%
“…Reporting is usually mandatory and a failure to report CSA is considered a crime [2,4,5]. However, the study by Menoch et al revealed insufficient medical knowledge of child abuse in residents' and practicing physicians' highlighting the need for increased education in child maltreatment [7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations